Helminth Diversity in Teleost Fishes from the Area of the Ukrainian Antarctic Station “Akademik Vernadsky”, Argentine Islands, West Antarctica - T. Kuzmina; I. V. Dykyy; O. O. Salganskij; O. I. Lisitsyna; E. M. Korol; Yu. I. Kuzmin (Zoodiversity, 2021)
Monitoring studies of the species diversity in marine ecosystems provide important data on ecological changes caused by global warming and anthropogenic influence. The present work was aimed to analyze the species diversity of the helminths parasitic in teleost fishes inhabiting the area near the Ukrainian Antarctic Station "Akademik Vernadsky" (Galindez Island, Argentine Islands, West Antarctica). During April – January of 2014–2015 and 2019–2020, 156 specimens of six fish species (Notothenia coriiceps, N. rossii, Chaenocephalus aceratus, Parachaenichthys charcoti, Trematomus bernacchii, and Harpagifer antarcticus) were examined. Totally, 21,166 specimens of 31 helminth species were collected and assigned to five taxonomic groups: Monogenea (1 species), Digenea (10), Nematoda (5), Cestoda (4), and Acanthocephala (11). Twenty-six helminth species were found in N. coriiceps,14 in N. rossii, 27 in P. charcoti, 23 in Ch. aceratus, 16 in T. bernacchii, and six in H. antarcticus. Larval stages of anisakid nematodes prevailed in helminth community of Ch. aceratus (66%) and P. charcoti (40%), while other fish species were mostly infected with acanthocephalans, trematodes and cestodes. The present data on the species diversity of helminth communities can be used as a baseline for long-term monitoring studies of fish parasites in the region of Argentine Islands.